Patient-Reported Outcomes Following Multi-Ligament Knee Injuries With or Without Internal Brace Augmentation and the Role of Patient Access to Rehabilitation (174). Issue 10 (31st October 2021) - Korber, Shane; Bolia, Ioanna; Benvergnu, Neilan; Panish, Brian; Juhan, Tristan; Weber, Alexander; Argintar, Evan; Hatch, George
Objectives: (1) To compare the postoperative outcomes in patient who underwent multifilament knee reconstruction (MLKR) with or without internal brace augmentation and (2) To examine potential differences in outcomes of patients with different access to postoperative rehabilitation following MLKR. Methods: Adult patients sustaining a multifilament knee injury (MLKI) from 2007 to 2020 who were surgically treated by a single surgeon were retrospectively identified and invited to participate. Patients with incomplete follow up data were excluded. Data recorded included patient demographics, intraoperative procedure performed (with versus without use of internal brace), patient access to rehabilitation after surgery (limited versus full access) and postoperative patient reported outcomes. The last included the Multiligament Quality of Life Questionnaire (MLQOL), PROMIS Computer Adaptive Testing (CAT) for Physical Function, Mobility, and Pain Interference, and the Lysholm Knee Questionnaire. Descriptive statistics were conducted using STATA. Comparison of the postoperative outcomes was performed between patients who received or did not receive internal brace during MLKR and those who had limited versus full access to postoperative rehabilitation, using descriptive statistics (STATA). The level of statistical significance was set at <0.05. Results: A total of 85 (15 females, 70 males) patients met the inclusion criteria. Of those, 62 patients (13 females, 49 males underwent MLKR without internal brace augmentation (NIB group) and 23 patients (2 females, 11 males) underwent MLKR with internal brace augmentation (IB group). Patient age and BMI were similar between the IB and NIB groups (Table 1). The mean follow-up time was 5.2+/-0.6 years on the NIB group and 1.5+/-0.1 years in the IB group (p<0.0001). The comparison of baseline characteristics and postoperative outcomes in MLKR patients in the NIB and IB groups is shown in Table 1. There was no difference in any of the postoperative outcome scores between patients in the NIB and IB groups who underwent MLKR. Access to rehabilitation data were available for 83 patients. Of those, 69 patients (12 females, 57 males) had full access to rehabilitation and 17 patients (3 females, 14 males) had limited access to postoperative rehabilitation. The mean follow- up time was similar between patients with versus limited access to rehabilitation (mean time was 2.6 years and 2.2 years respectively, p=0.96). The baseline patient characteristics were similar between the last two subgroups. However, patients with limited access to postoperative rehabilitation had significantly lower PROMIS Pain (p=0.018) and PROMIS Physical Function (p=0.025) scores compared to patients with full access to rehabilitation. The comparison of baseline characteristics and postoperative outcomes in MLKR patients with limited versus full access to postoperative rehabilitation is presented in Table 2. Conclusions: Internal bracing augmentation did not result in significant improvement of postoperative outcomes in patients undergoing MLKR, compared to the traditional technique without the use of internal brace, at short-term follow up. Postoperative rehabilitation is critical in patients who undergo MLKR, as patients with limited access to may experience worse outcomes at short term follow up in comparison to those who have full access to rehabilitation services. The socioeconomic status of the MLKR candidates should be examined preoperatively, and efforts should be made to grant these patients access to postoperative rehabilitation in order to optimize their clinical outcomes.